2007
DOI: 10.1271/bbb.60465
|View full text |Cite
|
Sign up to set email alerts
|

Ingestion of Difructose Anhydride III Enhances Absorption and Retention of Calcium in Healthy Men

Abstract: We examined the effects of a nondigestible disaccharide difructose anhydride III (DFAIII) on calcium absorption and retention by means of a human balance study of single-blind crossover design. Twelve healthy male subjects ingested 250 mg of shell powder as calcium carbonate (corresponding to 100 mg of calcium) with or without 1.0 g DFAIII three times a day for 13 d. In the last 4 d as a balance period, all urine and feces were collected and evaluated for calcium excretion. The apparent calcium absorption (mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 40 publications
0
20
0
1
Order By: Relevance
“…Moreover, DFA III has beneficial effects on nutrient absorption through the paracellular pathway by improving the opening of intestinal epithelial tight junctions (Mineo et al, 2002). Increased mineral absorption has been observed with DFA III supplementation in rats (Mineo et al, 2004), humans (Tomita et al, 2007), and cattle (Teramura et al, 2015a,b). In our previous study (Sato et al, 2012), we demonstrated that the addition of DFA III to maternal colostrum improved the efficiency of IgG absorption in 4 experimental groups of Holstein and Holstein/Japanese Black crossbred calves.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, DFA III has beneficial effects on nutrient absorption through the paracellular pathway by improving the opening of intestinal epithelial tight junctions (Mineo et al, 2002). Increased mineral absorption has been observed with DFA III supplementation in rats (Mineo et al, 2004), humans (Tomita et al, 2007), and cattle (Teramura et al, 2015a,b). In our previous study (Sato et al, 2012), we demonstrated that the addition of DFA III to maternal colostrum improved the efficiency of IgG absorption in 4 experimental groups of Holstein and Holstein/Japanese Black crossbred calves.…”
Section: Introductionmentioning
confidence: 99%
“…According to Kim et al (2001) investigation, heating in natural conditions even in moderate temperature (≥80°C) leads to inulin gel formation lowering due to the breakdown of long-chain to shorter chain inulins that are not able to form a gel. However, in pyrolysis (thermochemical decomposition) of inulin at elevated temperatures, di-fructose dianhydrides are produced which not only increase iron (Garsia-Moreno et al 2008) and calcium (Tomita et al 2007) absorption but also have technical benefit due to their strength structure and hydrophilicity (Godshall 2001). Generally, it is illustrated that potency of inulin gel formation is affected by many factors including inulin structure (DP) and concentration, pH, ion presence and another component such as hydrocolloids (Silva and Meireles 2015).…”
Section: Heat Stability and Gel Formationmentioning
confidence: 99%
“…El mismo grupo poblacional obtuvo un aumento de la absorción aparente de Ca (43%) y, por encima de todo, una mayor retención del mineral tras la ingesta de anhídrido de difructosa III (DFAIII), un disacárido no digerible extraído de la remolacha. Este estudio concluye que el aumento de la absorción de Ca a través de DFAIII, preferentemente promueve la formación ósea, más que la disminución de la reabsorción (debido al aumento de la osteocalcina más que la disminución de la Deoxipiridinolina) 64 .…”
Section: Estudios Realizados En Humanosunclassified